LITERATUR REVIEW: MENGKAJI EFEKTIVITAS PEMBERIAN MENTIMUN TERHADAP PENURUNAN TEKANAN DARAH - Arum Meiranny; Astri Syahirani (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
Introduction: Hypertension is a degenerative disease. Those aged ?55 years are at risk for suffering from hypertension, previously blood pressure prehypertension before being diagnosed with hypertension occurred between the third and fifth decades. The World Health Organization reports as many as 839 million cases of hypertension, by 2025 this figure is expected to increase to 1.15 billion or around 29% of the world's total population, where female sufferers are more than 30% compared to male hypertension sufferers, namely 29%. One of the non-pharmacological treatments to treat hypertension is consuming cucumber. Methods: International and national literature searched through electronic media with keyword hints. Eight articles were selected, each of which represents an effectiveness of giving cucumber to reduce blood pressure and provides various information. Results: There was an effect of giving cucumber on reducing blood pressure in respondents. Discussion: One alternative that can be used to lower blood pressure is by consuming cucumber. The diuretic effect on cucumber causes the salt content in the blood to decrease. Reduced levels of salt that absorbs or retains water will reduce blood volume so that it can lighten the work of the heart in pumping blood, and eventually blood pressure will decrease. Conclusion: The conclusion based on the analysis that has been done is that cucumber is effective for lowering blood pressure.